2014
DOI: 10.1159/000363175
|View full text |Cite
|
Sign up to set email alerts
|

Daily Protein Intake and Patient Outcomes in Severe Acute Kidney Injury: Findings of the Randomized Evaluation of Normal versus Augmented Level of Replacement Therapy (RENAL) Trial

Abstract: Background and Aims: We aimed to examine the association between dailyprotein intake (DPI) and outcomes in patients from the Randomized Evaluation of Normal versus Augmented Level (RENAL) trial. Methods: We analyzed the association between DPI and clinical outcomes using multivariable logistic regression, Cox proportional hazards models and time-adjusted analysis. Results: During ICU stay, mean DPI was 37.6 g/day among survivors and 37.7 g/day among nonsurvivors (p = 0.96; DPI of 0.5 g/kg/day). Only 159 (10.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
2
23
1
1
Order By: Relevance
“…Inadequate DPI in highly catabolic AKI patients may cause progressive lean body mass loss leading to protein-energy wasting (PEW), cachexia, and poor clinical outcome [ 14 ]. Of note, the mean DPI in our study was 0.6 g/kg/day which was quite similar to a recent post hoc analysis of the RENAL study [ 13 ]. In contrast to our results, such study found that a lower DPI was not associated with increased 90-day mortality or any secondary outcomes (28-day mortality, death in the ICU, in-hospital death, RRT outcome, duration of ICU and hospital stays, duration of mechanical ventilation and RRT, dialysis status at day 90, and any new organ failures).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Inadequate DPI in highly catabolic AKI patients may cause progressive lean body mass loss leading to protein-energy wasting (PEW), cachexia, and poor clinical outcome [ 14 ]. Of note, the mean DPI in our study was 0.6 g/kg/day which was quite similar to a recent post hoc analysis of the RENAL study [ 13 ]. In contrast to our results, such study found that a lower DPI was not associated with increased 90-day mortality or any secondary outcomes (28-day mortality, death in the ICU, in-hospital death, RRT outcome, duration of ICU and hospital stays, duration of mechanical ventilation and RRT, dialysis status at day 90, and any new organ failures).…”
Section: Discussionsupporting
confidence: 90%
“…Studies in the 1990s and early 2000s had used old-fashioned CRRT technique and did not mention the association between nutritional parameters and clinical outcomes [ 10 12 ]. In the post hoc analysis of R andomized E valuation of N ormal versus A ugmented L evel (RENAL) study [ 13 ], low DPI did not show the association of low DPI and the poor clinical outcome. Therefore, there are still conflicting results in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations from international critical care guidelines suggest that critically ill patients should receive at least 1.2 g/kg body weight per day of protein via the enteral protein targets, with several studies reporting that during usual critical care management, patients only receive a mean of 0.6-0.8 g/kg per day protein, presumably because of interruptions to feeding, intolerance, and limited availability of higher-protein formulas. [5][6][7][8][9] During critical illness, the frequent occurrence of muscle loss is associated with inferior patient-centered outcomes. 3 Inflammatory mediators, coupled with inactivity, may drive an imbalance between protein breakdown and synthesis, 10,11 with rapid muscle loss of up to 1%-2% of lean body mass per day.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the RENAL study received a low DPI (0.5 g/kg/day), markedly below current recommendations. However, a low DPI was not independently associated with a decreased risk of death at 90 days or an increase in mechanical ventilation, RRT, ICU, or hospital-free days [36]. Thus, as with DCI, data is not clear on the optimal DPI target in AKI patients.…”
Section: Nutritional Support In Akimentioning
confidence: 92%